HUMAN RIGHTS AND PANCASILA: INDONESIA’S APPROACH TO RELIGIOUS FREEDOM - Takasanakeng, Elvira Stefanie (Journal of Studia Legalia, 2025)
This paper explores the complex relationship between Indonesia’s national philosophy, Pancasila, and the international human rights standard of religious freedom. While Indonesia has ratified the International Covenant on Civil and Political Rights (ICCPR), its domestic interpretation of religious freedom is significantly shaped by Pancasila’s emphasis on harmony, belief in God, and social harmony. This two central questions this paper attempt to answer are whether Indonesia can uphold universal human rights without compromising its philosophical values, and whether religious belief should be legally limited to preserve social harmony. While previous scholarship has focused primarily on legal frameworks and institutional roles, this paper explores a different approach by analyzing the philosophical tensions between Pancasila and universal human rights. Through legal and normative analysis, it finds that while the principles of Pancasila are not inherently opposed to international law, the way they are applied often leads to marginalization and structural discrimination, particularly against religious minorities. The paper also argues that the country’s use of social harmony to justify limitations on belief shifts the law from neutrality to control. Ultimately, it concludes that Indonesia can reconcile Pancasila and international human rights law, but only by reinterpreting social harmony as a product of justice and pluralism, not uniformity.